Nutrição e análise do perfil transcriptômico por RNA-seq em arroz submetido à aplicação de bioestimulantes - Vasconcelos, Ana Carolina Pereira de (2023)
Although studies have already been conducted with the use of biostimulants in different cultures, the results obtained have been controversial and with little scientific basis, with the need for further investigations regarding nutritional efficiency and gene expression, for better elucidation of the results obtained. The objective of this work was to study the use of biostimulants in rice plants (Oryza sativa L.), investigating their effects on nutritional responses, vegetative growth and gene expression through RNA sequencing analyses (RNA-seq). The first chapter aimed, from a literature review, to discuss the use, concepts, setbacks and benefits of biostimulants in Brazilian agriculture and the use of the transcriptomic analysis technique to identify and validate potential biomarkers, as well as the importance and use of Oryza sativa L. as a model for gene studies. The following chapters consisted of the presentation and discussion of the data obtained in this study. Thus, in Chapter 2, two biostimulants in their commercial doses, a monosylícic acid (in the testing phase for later registration with the Ministry of Agriculture) and a control were evaluated. The experiment was carried out in a greenhouse, belonging to the Federal University of Uberlândia (UFU). Pots with 10 dm3 of soil classified as Quartzarenic Neosol were used, using the cultivar BRS Primavera. The products were applied via leaf, in the V4 development stage. The experimental design was completely randomized, with six replications. The dry matter mass of the shoots and the contents and accumulation of macro and micronutrients were determined. The statistical assumptions of the data obtained were tested, with the Kolmogorov-Smirnov normality tests and the homogeneity of levene variances, both at 0.01 significance and submitted to variance analysis by Tukey test, at 0.05 of significance. In general, the application of biostimulants and monosylícic acid alters the leaf contents of calcium, manganese, boron and copper. In Chapter 3, the experiment was carried out in a greenhouse, belonging to the UFU. Pots with 10 dm3 of soil classified as Quartzarenic Neosol were used, using the cultivar BRS Primavera. A biostimulant was evaluated, applied via leaf, in the development stage V4. The experimental design was completely randomized, with three biological replications. The collection of plant material was performed at the reproductive stage (R4). The samples were collected and immediately frozen in liquid N2, stored at -80º C and sent for cell transcriptome (RNA-seq). Bioinformatics analysis was performed for the analysis of molecular data. Differential expression analyses identified 498 genes differentially expressed in leaf tissue of Oryza sativa L., when treated with the biostimulant. For up-regulated genes, it was observed the increase in gene expression closely related to defense mechanisms, stress responses, flowering, gene transcription/translation regulation and plant metabolism. For down-regulated genes, it was possible to observe mainly genes related to photosynthesis, stress responses, plant development and floral regulation.